„Paru słówek igraszką unieśmiertelnić wroga” – o pamfletach Juliana Tuwima - Stępień, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article presents both the formal aspects of the poetics of Tuwim’s pamphlets (enumeration, hyperbole, grotesque, irony) and the figures of those who are the targets of his satirical addresses. Tuwim used verse satires to create polemical and ironic portraits of individual people (the main figure being a nationalist journalist and literary critic Stanisław Pieńkowski) as well as to ridicule state institutions, ideologies and political parties. The author also analyses pamphlet-like lyrical poems, columns and literary criticism by Julian Tuwim. In conclusion the author describes some elements of the cultural milieu which the poet refers to in his satirical writing (popular culture and the media, totalitarian ideologies, mass-society).